Faktor-Faktor yang Berhubungan dengan Kinerja Perawat di Rumah Sakit Islam PDHI Yogyakarta - Supriadi Supriadi (STIKes Surya Global Yogyakarta, 2017)
Background: The era of globalization requires hospitals to improve the quality of health services. Efforts to improve the quality of health services can not be separated from efforts to improve the quality of nursing services because nurses are the most numerous health workers in hospitals that provide continuous service for 24 hours. The quality of nursing services describes the performance of nurses. The performance of a nurse can be judged by the quality of nursing care given to the patient. The performance of nurses can be influenced by various factors such as motivation, work ethic, work environment, competence, job satisfaction. Objective: The general objective of this research is to know factors related to Nurse Performance at Yogyakarta Islamic Hospital PDHI. And the specific objective of this research is to know the relationship motivation, work ethic, work environment, competence, job satisfaction with performance Nurse at Yogyakarta Islamic Hospital PDHI. Method: The research design in this research is descriptive correlation research with cross sectional approach. Population in this research is Nurses at Yogyakarta Islamic Hospital PDHI amounted to 128 people. Sampling technique used was purposive sampling with inclusion and exclusion criteria obtained by a sample of 51 respondents. Data analysis used statistical test of kendall’s tau and multiple linear regression with significance level 5%. Result : Result of research got all variable that is motivation, work ethic, work environment, competence and job satisfaction influence nurse performance with p value 0,011, 0.000, 0,018, 0.000, 0.000 (P 0.05). Multivariate test obtained sig value. 0.000, which means simultaneously independent variables associated with the performance of nurses.